2006
DOI: 10.1074/jbc.m602393200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of FlaA1 from Helicobacter pylori Reveal the Mechanism for Inverting 4,6-Dehydratase Activity

Abstract: FlaA1 from the human pathogen Helicobacter pylori is an enzyme involved in saccharide biosynthesis that has been shown to be essential for pathogenicity. Here we present five crystal structures of FlaA1 in the presence of substrate, inhibitors, and bound cofactor, with resolutions ranging from 2.8 to 1.9 Å . These structures reveal that the enzyme is a novel member of the short-chain dehydrogenase/reductase superfamily. Additional electron microscopy studies show the enzyme to possess a hexameric doughnut-shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
77
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 49 publications
3
77
0
Order By: Relevance
“…Thus, Z= is reflective of both the assay signal dynamic range and the data variation associated with the signal measurements and is used for comparison and evaluation of the quality of assays. A high-throughput assay with a 1 Ͼ Z= Ͼ 0.5 score is considered an excellent assay (28). Therefore, results from the plates with Z= Ͼ0.5 were analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Z= is reflective of both the assay signal dynamic range and the data variation associated with the signal measurements and is used for comparison and evaluation of the quality of assays. A high-throughput assay with a 1 Ͼ Z= Ͼ 0.5 score is considered an excellent assay (28). Therefore, results from the plates with Z= Ͼ0.5 were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been demonstrated that all five Pse pathway enzymes can be combined in a single one-pot reaction for the synthesis of Pse using UDPGlcNAc as an initial substrate (22). Structural studies of three of the biosynthetic enzymes have also been completed (26)(27)(28).…”
mentioning
confidence: 99%
“…Two homologous proteins, FlaA1 and PseB (46% and 49% similarity to the B. subtilis NDmed YpqP protein, respectively) (see Fig. S1 in the supplemental material), have been characterized biochemically as UDP-N-acetylglucosamine 5-inverting 4,6-dehydratases, which catalyze the first step in the biosynthesis of pseudaminic acid in Helicobacter pylori and Campylobacter jejuni (60,61). Complementary analytical analysis would be needed to determine if B. subtilis can produce pseudaminic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data indicate that, in addition to UDP-4-keto-6-deoxy-GlcNAc, Cj1293 also generates UDP-2-acetamido-2,6-dideoxy-␤-L-arabino-4-hexulose (25) via a change of chirality at carbon 5 during the dehydration step. Structural studies of a homologous enzyme from Helicobacter pylori, FlaA1, indicate that the formation of the 4-keto-arabino intermediate is enzymatically catalyzed but that of the 4-keto-gluco intermediate is not and occurs via enolization of a double bond between C-4 and C-5 (26) (Fig. 1).…”
mentioning
confidence: 99%